2018
DOI: 10.1016/j.jpcs.2018.03.025
|View full text |Cite
|
Sign up to set email alerts
|

On the calculation of the inverse isotope effect in PdH(D): A Migdal-Eliashberg theory approach

Abstract: Replacement of hydrogen by deuterium in palladium hydride results in higher superconducting temperatures and an anomalous isotope effect that has not been yet fully explained. In this work, we try a new approach to the explanation of the inverse isotope effect in PdH(D). Our approach introduces two new aspects. First, we took into account the experimental evidence that at temperatures below 50 K, the crystal structure of PdH and of PdD is zincblende. Second, we take into account not only the influence of the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Yussouff et al [7] extended this discovery on palladium-hydrogen-deuterium-tritium system (PdHx-PdDx-PdTx). This reverse isotope effect in PdHx-PdDx-PdTx system is still under wide discussion [8,9]. In regard of considered in this paper ThH-ThD system, detailed studied by Caton and Satterthwaite [10] showed that superconductors in thorium-hydrogen-deuterium (ThH-ThD) system have reverse isotope effect, and Dietrich et al [11] showed that transition temperature, Tc, of the Th4H15 phase has linear positive ramp of 0.42 K/GPa versus applied external pressure.…”
Section: Introductionmentioning
confidence: 85%
“…Yussouff et al [7] extended this discovery on palladium-hydrogen-deuterium-tritium system (PdHx-PdDx-PdTx). This reverse isotope effect in PdHx-PdDx-PdTx system is still under wide discussion [8,9]. In regard of considered in this paper ThH-ThD system, detailed studied by Caton and Satterthwaite [10] showed that superconductors in thorium-hydrogen-deuterium (ThH-ThD) system have reverse isotope effect, and Dietrich et al [11] showed that transition temperature, Tc, of the Th4H15 phase has linear positive ramp of 0.42 K/GPa versus applied external pressure.…”
Section: Introductionmentioning
confidence: 85%
“…where R (ω) is given by and the T c functional derivative respect to the Eliashberg function is expressed as [46,47,49,50]…”
Section: Computational Detailsmentioning
confidence: 99%
“…For LaH 10 a value of α ∼ = 0.47 at 150 GPa has been observed 10 , whereas in H 3 S it has a very large value of α ∼ = 2.37 at 130 GPa, decreasing it rapidly as pressure increases up to 230 GPa (α ∼ = 0.29). While for PdH there are in literature several theoretical and experimental publications studying and discussing the nature of its inverse isotope effect [34][35][36][37][38] , for H 3 S there are just a few theoretical reports that address this topic 14,20,[39][40][41][42] , but without a proper discussion of the nature of such interesting phenomena or quantitative analysis of α.…”
Section: Introductionmentioning
confidence: 99%
“…For α, we take into account the changes in the electron-electron interaction coming from the isotope mass substitution, in addition to the electron-phonon interaction. Then, the isotope coefficient is splitted into two contributions, each of them to their corresponding interaction 34,35,51 . This formalism has successfully explained the inverse isotope effect in PdH at ambient pressure 35 , as well as its behavior under pressure 34 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation